Detection of Crossed Walls Security Alarm System against Invasion - Baballe, Muhammad Ahmad (Review of Computer Engineering Research, 2021)
A security detection system was developed to secure any of the walls that were crossed. These walls are the north, east, south and, west wall. These walls are designed to be in a square environment, each of these walls has a Light Emitting Diode (LED) that functions as a transmitter and a Light Dependent Resistor (LDR) that function as a Receiver. A closed-circuit television (CCTV) was used to capture the real-time video of any of the crossed walls. A Liquid Crystal Display (LCD) was used to display the status of these walls and display the name of the crossed walls. A magnetic buzzer is also used to alert the security personnel after a system has displayed the name of the crossed wall on the LCD. A Microcontroller (PIC16F877A) is used as the brain of the developed security system. The Personal Computer (PC) is also used to display the system status through personal computer Parallel Port, to display the real-time video captured by the CCTV camera, saving the video on personal computer hard drive, and to control the developed system from the personal computer (PC) such as activating, deactivating and resetting the developed system. With the aid of the latest development in technology nowadays, it is possible to secure the properties and people’s lives using a security detection system that will monitor, guide, and protect the environments that need to be secure against burglars and abductors.